Preschool teachers' needs for vegetable and fruit learning modules - Nur Suhaidah Sukora; Sumira Amir; Connie Cassy Ompok; Noraini Said; Jusiah Idang (Human Resource Management Academic Research Society, 2025)
This study was conducted to identify Preschool teachers' perceptions of the need for a vegetable and fruit learning module for 5-6-year-old children. The study employed a quantitative approach in the form of a survey for data collection and analysis. The survey method involved the use of a questionnaire through Google Form. A total of 30 Early Childhood Education teachers in Kota Kinabalu, Sabah participated in this study. The findings of the study indicate that the component with the highest score is the Teachers’ Teaching Module Needs component was (M = 4.83, SD = 0.45). While, the Teaching and Learning Content and Preschool Student Activities Component scored the lowest with a score of (M=4.73, SD=0.47). The results of this study suggest that Preschool teachers perceive the need for a vegetable and fruit learning module as important for 5-6-year-old children. Teachers also believe that the presence of this module in preschool is crucial for providing early exposure to the importance of consuming nutritious and balanced food for their growth. In this study, teachers need to implement the vegetable and fruit learning module so as to provide engaging learning materials to enhance student-centered learning development.